2020
DOI: 10.1038/s41598-020-71784-3
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and risk of tuberculosis among people living with HIV in whom TB was initially ruled out

Abstract: Tuberculosis (TB) misdiagnosis remains a public health concern, especially among people living with HIV (PLHIV), given the high mortality associated with missed TB diagnoses. The main objective of this study was to describe the all-cause mortality, TB incidence rates and their associated risk factors in a cohort of PLHIV with presumptive TB in whom TB was initially ruled out. We retrospectively followed a cohort of PLHIV with presumptive TB over a 2 year-period in a rural district in Southern Mozambique. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
(47 reference statements)
1
8
0
1
Order By: Relevance
“… 8 Adults 2383 7736.8 70 0.905 42. East Africa García JI, et al [ 101 ], 2020 Mozambique Retr. 2 Both 382 685.2 37 5.4 43.…”
Section: Resultsmentioning
confidence: 99%
“… 8 Adults 2383 7736.8 70 0.905 42. East Africa García JI, et al [ 101 ], 2020 Mozambique Retr. 2 Both 382 685.2 37 5.4 43.…”
Section: Resultsmentioning
confidence: 99%
“…9 Our results showed that HIV patients never tested for LTBI and those who tested positive at the first instance were at higher risk of TB disease development. 10…”
Section: Discussionmentioning
confidence: 99%
“…Some patients with respiratory symptoms may have received antibiotic treatment (with drugs other than for TB) prior to TB diagnosis and, although this is relatively rare in our setting, we did not collect these data in all presumptive TB patients. An improved understanding of the underlying causes of the spectrum of disease in SCs is especially important to not only the TB field in general [55,56] but especially for microbiome research. Lastly, our objective was to comprehensively characterise the microbiome pretreatment (before the confounding effects of antibiotics), however, future research on the long-term effects of TB treatment on the microbiome is important, including its link with recurrence.…”
Section: Discussionmentioning
confidence: 99%